(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The intensity of termoshock proteins biosynthesis in yeasts Candida rugosa BCB-925 was investigated. It has been shown that under high temperature (44°C) the synthesis of comparatively low-molecular proteins (M<78 kDa) is 2–3 times more intensive than of high-molecular proteins.